2017
DOI: 10.1097/jcn.0000000000000390
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Self-management Knowledge and Support on the Relationships Among Self-efficacy, Patient Activation, and Self-management in Rural Patients With Heart Failure

Abstract: Background: Self-management (SM) is an essential component of heart failure (HF) management. The mechanisms to improve SM behaviors are unclear. Objective: The objective of this study is to examine whether patient activation mediates the effect of self-efficacy on SM behaviors in rural HF patients. Methods: A secondary analysis was conducted using data collected from a randomized controlled trial aimed to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 46 publications
2
17
0
1
Order By: Relevance
“…The observed improvement in activation among participants who received the intervention (IG) is consistent with previous reports (Roberts et al, 2016;Wolever & Dreusicke, 2016;Young, Kupzyk, & Barnason, 2017) and supports the idea that HC is a useful, nondisease-specific method for improving activation in people with chronic conditions, even in the presence of multimorbidity. As to why the improvement in activation was not maintained across follow-up, | 465 the intervention may have been too short to allow for consolidation of change, insofar as those HC interventions that have been found to be effective in follow-up assessments were longer than ours both in number of sessions and overall length of the program (Park et al, 2017;Sharma et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…The observed improvement in activation among participants who received the intervention (IG) is consistent with previous reports (Roberts et al, 2016;Wolever & Dreusicke, 2016;Young, Kupzyk, & Barnason, 2017) and supports the idea that HC is a useful, nondisease-specific method for improving activation in people with chronic conditions, even in the presence of multimorbidity. As to why the improvement in activation was not maintained across follow-up, | 465 the intervention may have been too short to allow for consolidation of change, insofar as those HC interventions that have been found to be effective in follow-up assessments were longer than ours both in number of sessions and overall length of the program (Park et al, 2017;Sharma et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Patient activation in supporting self-management strategies (Aung et al, 2016) is a self-reported measure of strength of self-management (Shively et al, 2013). Given the complex relationships among patient activation and self-management, the PAM measure has been shown effective as the method in quantifying the patient’s ability to conduct self-management (Young et al, 2017). A challenge in using the PAM-13 is the licensing fee for conducting studies in small centers, with licensing fees available at https://www.insigniahealth.com/products/pam-survey (Shively et al, 2013; Titova et al, 2017; Turner et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…When studies on patient activation were synthesized in a systematic review of randomized controlled trials, interventions that improved patient activation significantly improved self-care in a variety of other chronic conditions 99 and for a variety of intermediate outcomes such as depression, anxiety, and self-efficacy 100 . Investigators studying the association between patient activation and HF self-care demonstrated that patients with HF who are more “active” engage in better self-care behaviors 101 regardless of their HF knowledge and health literacy 102 and that patient activation mediates the relationship between self-efficacy and self-care when HF self-care knowledge is low 103 …”
Section: Problem Person and Environmental Factorsmentioning
confidence: 99%